BIOLOGY TEACHERS IN THE MIDDLE SCHOOL TEACHING SKILLS PRACTICE - Assistant.Prof. samaa Ibrahim Abdullah (European Journal of Humanities and Educational Advancements, 2024)
The current research aims to observe the extent to which biology teachers in the middle school practice some teaching skills. The research community consisted of ( 127 ) intermediate and secondary schools by (30) schools as a research sample, which constitutes (43%) of the total schools of the research community. The number of middle schools reached (21) schools and (9) secondary schools. For the purpose of verifying the validity of the skills included in the observation form for application in measuring the performance of biology teachers for the middle school and the validity of its formulation, it was presented to a group of arbitrators and specialists to find honesty and verify reliability, and thus the tool became valid for field application.